The 25th Anniversary of the Lithuanian Society of Palliative Medicine - Šeškevičius, Arvydas (Slauga. Mokslas ir praktika, 2021)
The Lithuanian Society of Palliative Medicine was founded in 1995. Its main goal is to promote the development of palliative care as a separate specialty and the systematic and consistent development of the provision of palliative care in Lithuania. On the initiative of the Society, an order of the Minister of Health was issued, allowing the establishment of palliative care institutions. In addition, studies in palliative medicine were introduced in colleges and universities, and qualification improvement courses, conferences, and publishing in in this field were initiated.